The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3892/etm.2015.2913
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcutaneous acupoint electrical stimulation on the imbalance of Th1, Th2, Th17 and Treg cells following thoracotomy of patients with lung cancer

Abstract: Abstract. An imbalance in the various T lymphocytes, including T-helper (Th) 1 , Th 2 and Th 17 cells, and regulatory T (T reg ) cells, has been associated with immune dysfunction, and may occur following thoracotomy of patients with lung cancer. The use of transcutaneous acupoint electrical stimulation (TAES) has previously been demonstrated to exert immunoregulatory effects; therefore, the present study aimed to evaluate whether TAES was able to attenuate postoperative immune suppression in patients with lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Studies demonstrated that acupuncture promoted the release of cytokines activated by NK cells and enhanced nonspecific antitumor immunity. 10 Additionally, a current study by Wu et al suggested that TAES was able to partially attenuate the postoperative immune depression of patients with lung cancer by regulating the balance of T lymphocytes and the expression levels of related cytokines and transcription factors, 15 but they did not discuss the impact of TEAS on NK cells and related immunologic factors, such as TNF-α and IL-6. Actually, NK cells play an all-star role in protecting hosts from carcinogenesis and metastases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies demonstrated that acupuncture promoted the release of cytokines activated by NK cells and enhanced nonspecific antitumor immunity. 10 Additionally, a current study by Wu et al suggested that TAES was able to partially attenuate the postoperative immune depression of patients with lung cancer by regulating the balance of T lymphocytes and the expression levels of related cytokines and transcription factors, 15 but they did not discuss the impact of TEAS on NK cells and related immunologic factors, such as TNF-α and IL-6. Actually, NK cells play an all-star role in protecting hosts from carcinogenesis and metastases.…”
Section: Discussionmentioning
confidence: 94%
“… 14 Therefore, NK cells, TNF-α, and IL-6 were selected as the immunological factors of interest. The TEAS has been proven to provide perioperative immune system protection by regulating the balance of T lymphocytes and the expression levels of related cytokines and transcription factors, 15 and the procedure may be a promising strategy for treating postoperative immunological dysfunction in patients with NSCLC. However, relevant studies regarding these effects are relatively lacking.…”
Section: Introductionmentioning
confidence: 99%
“…After the return of spontaneous circulation (ROSC), CA patients with systemic ischemia/reperfusion injury (IRI) can manifest 'sepsis-like' syndromes and immune disorders which can lead to infections (3)(4)(5). CD4 + T lymphocytes are effector cells in the adaptive immune system of humans and play important roles in ghting infections and the pathogenesis of IRI (6,7). Upon activation of the T cell receptor (TCR), naïve CD4 + T lymphocytes differentiate into T-helper 1 (Th1), and Th2 subsets (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to understand the mechanisms of pain and the possible effectiveness of TENS in enabling increasingly effective treatments, recent studies have noted that in addition to analgesia, TENS may have an effect on the circulatory [ 7 , 8 ], healing [ 9 , 10 ], and inflammatory systems [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%